Heritage For Sustainable Development Goals: Where Are We Now? - Tanudirjo, Daud Aris (Jurusan Sejarah, Seni, dan Arkeologi, FKIP, Universitas Jambi, 2024)
This article explain about Heritage For Sustainable Development Goals: Where Are We Now?